Method for dense deposition of lithium on conductive substrate
By forming a lithium-philic intermediate layer on the conductive substrate and contacting the liquid lithium/ammonia composition with the intermediate layer, removing ammonia to deposit a dense lithium layer, the problem of difficult to simplify, low-temperature and easy-to-scaling production of thin lithium foils or lithium coatings in the prior art is solved, and efficient and economical thin lithium electrode production is achieved.
Patent Information
- Application Number
- CN202380061078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-23
- Filing Date
- 2023-07-24
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to simplify, low temperature and easy to expand the production of thin lithium foils or lithium coatings, especially in the production process of thin lithium electrodes requiring high capacity and energy density in lithium batteries.
By forming a lithium-philic intermediate layer on the conductive substrate and contacting the liquid lithium/ammonia composition of Li(NH3)4+x with the intermediate layer, the ammonia is then completely removed to deposit a dense lithium layer. The method includes forming a lithium-philic intermediate layer using processes such as physical vapor deposition, electrochemical thin film deposition, or mechanical application of gold foil.
The production of thin, uniform and dense lithium coatings at a mild temperature is achieved, solving the problems of complex process, high cost and difficult to expand in the prior art, and improving the capacity and energy density of lithium batteries.
Abstract
Description
[0001] The present invention relates to a method for producing a lithiophilic interlayer on a conductive substrate and subsequently depositing dense lithium on such an interlayer. Thus, such a lithiophilic coated substrate can be used as a substrate for use with a lithium-ion battery having a composition of Li(NH3) 4+x The invention also relates to a substrate coated with a lithiophilic intermediate layer and dense lithium. Background Art
[0002] Currently commercially available lithium batteries work according to the intercalation principle. A graphite material (corresponding to the formula LiC6) with a maximum capacity of 372 mAh / g is used as the negative electrode. Higher capacity and energy density can be achieved by partially or completely replacing graphite with alloy active materials such as silicon or tin ("anode material"), or completely replacing graphite materials with metallic lithium.
[0003] For the production of thin lithium electrodes with a lithium thickness of <30 μm required for future lithium metal batteries, the usual extrusion process is not suitable. Or it is disadvantageous because cost-intensive processes have to be used, such as a combination of extrusion and high-precision rolling, PVD technology (plasma vapor deposition) or processes operating at higher temperatures (e.g. lithium melt deposition on current collectors at >180°C).
[0004] Therefore, simplified, low-temperature, and easily scalable processes are needed to produce thin lithium foils or lithium coatings.
[0005] Alkali metal solutions, especially solutions of metallic lithium in liquid ammonia, have long been known (e.g. WC Johnson, MM Piskur, J. Phys. Chem. 37 (1933) 93-99). When a saturated lithium solution is cooled to <-60°C, phase separation occurs and a layer of metallic bronze liquid (Li (NH3) 4, called lithium bronze) is formed on the dilute blue solution (H. Jaffe, Z. Phys. 93, 1935, 741-761). The lithium / ammonia system is described in detail in R. Hoffmann et al., Angew. Chem. Int. Ed. 2009, 48, 8198-8232. Due to the presence of free electrons, these liquids have high electrical conductivity similar to that of metals, so they belong to the class of electronic compounds.
[0006] J. Bronn (“Liquefied ammonia as a solvent”, December 31, 1905, Julius Springer, Berlin, ISBN 978-3-642-50511-9, DOI: 10.1087 / 978-3-642-50821-9, pages 116-117) describes that ammonia can be removed from “lithium ammonium” under vacuum conditions at +50 to +60° C. to produce crystalline lithium metal.
[0007] GB 642 034A describes an electrochemical process for the production of alkali and alkaline earth metals. In this process, lithium salts are electrolyzed in liquid ammonia or the like to obtain a liquid or pasty lithium / ammonia adduct. In a second step, lithium metal can be obtained by evaporating ammonia at low temperatures. The metal is obtained in the form of a sponge-like substance (page 7, lines 35-47).
[0008] WO 2021 / 245196 Al describes a process for producing lithium metal and lithium alloy shaped bodies from an ammoniacal lithium metal solution. In this process, the composition is Li(NH3) 4+x The metallic lithium ammonia solution with x=0-10 is contacted with a metal or conductive deposition substrate, and ammonia is removed by inert gas overflow at a temperature of -100 to 100°C or at a pressure of 0.001 to 700 mbar, so that the remaining lithium is deposited on the deposition substrate or / and it is doped with lithium or alloyed with lithium.
[0009] Purpose
[0010] The object of the present invention is to provide a scalable method for producing thin, uniform and dense lithium coatings on substrates with good electronic conductivity, such as metal or carbon-based films, which method can also be carried out at mild temperatures. In addition, substrates provided with thin, uniform and dense lithium coatings should be provided. DETAILED DESCRIPTION
[0011] The lithium-coated substrate of the present invention is prepared by making the composition of Li(NH3) 4+x and x=0-10 in contact with a conductive substrate (e.g. a metal-based or carbon-based foil), wherein the metal-based or carbon-based substrate (usually a foil) to be coated with lithium is in a lithiophilic form, i.e., it is easily wetted by elemental lithium by applying a metal-containing intermediate layer.
[0012] The lithiophilic interlayer consists of a 1-5000 nm, preferably 5-1000 nm thick, metal-based or carbon-based substrate / foil coating having at least one metal or metalloid element capable of forming an alloy with lithium. This element is selected from the group Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ge, Ga, In, Mg, Cr, V, Mo, W, Zr, Mn. Preferred elements are Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ga, In and Mg. Particularly preferred elements are Zn, Al, Au, Si, Sn, Ga and. These elements are present either in pure form or in the form of a mixture of at least two of the mentioned elements. The lithiophilic coating is applied to at least one side of the substrate / foil, preferably to all sides or both sides.
[0013] The dense lithium-coated conductive substrate according to the present invention is composed of a flaky metal or a flaky carbon-based material, and at least one side of the substrate has a 1 to 5000 nm thick lithium-philic interlayer, and the lithium-philic interlayer contains at least one metal or metalloid element selected from Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ge, Ga, In, Mg, Cr, V, Mo, W, Zr, and Mn or is composed of the at least one metal or metalloid element.
[0014] According to the present invention, the method for preparing a substrate composed of a sheet metal or a sheet carbon-based material from a composition of Li(NH3) 4+x A method for depositing dense lithium from a liquid lithium / ammonia composition, wherein x=0-10, characterized in that the conductive substrate is coated on at least one side with a 1-5000 nm thick lithiophilic intermediate layer, the intermediate layer containing at least one element selected from the group consisting of Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ge, Ga, In, Mg, Cr, V, Mo, W, Zr, Mn, or consisting of at least one such element, and the structure is similar to that of Li(NH3) 4+x contacting with a lithium / ammonia composition wherein x=0-10, and subsequently completely removing the ammonia.
[0015] According to the invention, the lithiophilic interlayer can be deposited by different processes, the most important of which are as follows:
[0016] 1. Physical vapor deposition (PVD). In this process, a substrate (e.g. foil) is sputtered with at least one lithium alloying element in a vacuum. When gold is used to build the intermediate layer, a thin (1-50 nanometers thick) nickel layer is preferably pre-plated on the conductive substrate, provided that the substrate itself is not made of nickel. The nickel layer acts as a diffusion barrier between the substrate and the gold layer.
[0017] 2. Electrochemical thin film deposition ("electroplating"). In this electroplating process, a solution of lithium alloying elements is electrolyzed, and a conductive substrate, usually in the form of a foil, serves as a cathode, on which the lithium alloying elements are deposited. According to the invention, before the subsequent lithium coating step, electrolyte residues must be removed by dripping, washing and (if necessary) drying.
[0018] 3. Mechanical application of a thin foil containing the desired lithiophilic metal. This process is particularly suitable for gold, since gold foils with very low layer thickness (i.e. <1 μm) are commercially available (e.g. from Nanjing Gold Foil Factory). In this case, improved large-area contact and adhesion of the two layers / foils can be achieved by appropriate mechanical post-processing processes (e.g. pressing, rolling, winding, etc.). In industrial applications, this is best achieved by automated roll-to-roll processes.
[0019] As substrates with good electronic conductivity, flat structures composed of copper, nickel, iron or films composed of or containing carbon nanotubes (CNT) or graphene are preferably used. Such substrates are usually used as conductive films in lithium batteries.
[0020] According to the invention, the layer thickness is determined by the SEM method (SEM = scanning electron microscope). The measurement is carried out in accordance with DIN EN ISO 9220 (Metallic coatings - Coating thickness measurement - Scanning electron microscopy). Very thin coating thicknesses (<100 nm) can also be measured using X-ray methods, in particular X-ray reflection technology (XRR). This technology is described by Miho Yasaka, The Rigaku Journal, 26 (2), 2010.
[0021] Next, the uniformly coated substrate / foil (ie, over the entire area with the intermediate layer) is contacted with a solution of pure metallic lithium in ammonia, preferably with a composition of Li(NH3) 4+x Pure liquid lithium bronze is contacted in the range of -40 to +40°C, preferably in the range of -10 to +30°C, more preferably in the range of +15 to +30°C, and particularly preferably at an ambient temperature of +20 to +30°C. For this purpose, the conductive substrate / foil provided with the lithiophilic intermediate layer is immersed in the liquid lithium / ammonia mixture. This can be done piece by piece with the aid of tweezers, for example, or continuously by a roll-to-roll process. Depending on the desired lithium layer thickness, the temperature and the type of lithiophilic coating, the contact time ranges from 0.1 to 10,000 seconds, preferably from 1 to 2,000 seconds. In the process, part of the ammonia is evaporated and an alloy consisting of lithium and the alloy-forming elements of the intermediate layer is formed in the contact area with the conductive lithiophilic substrate, or / and metallic lithium is deposited in pure form on the intermediate layer. The lithium alloy layer is generally formed with a gradually decreasing concentration of the alloy-forming elements towards the outside.
[0022] The formation and deposition of lithium onto the conductive substrate / foil provided with the lithiophilic interlayer is then completed by quantitative removal of ammonia. This step is carried out at a temperature of -40°C to +100°C, preferably -10 to +60°C, more preferably +15 to +30°C, particularly preferably at an ambient temperature of +20 to +30°C, preferably under reduced pressure, i.e. in a pressure range of 0.001 to 700 mbar. Alternatively, ammonia can also be removed by passing an inert gas stream. Since the stripping gas (inert gas stream) reduces the ammonia concentration and makes the recovery of ammonia more difficult, this process is generally less cost-effective than a vacuum process. After complete removal of ammonia, elemental lithium metal remains on the lithiophilic deposition substrate in the form of a thin, uniform (bonded), areal, dense layer.
[0023] With the process according to the invention, metallic lithium is deposited on the lithiophilic interlayer in a layer thickness of 0.01 to 50 μm, preferably 0.1 to 30 μm, particularly preferably 0.5 to 25 μm, as determined by SEM.
[0024] Surprisingly, it was found that under these conditions, pure metallic lithium is deposited in a thin, uniform (coherent) dense form over the entire area of the lithiated surface according to the invention. The compactness of the lithium can be characterized by measuring the specific surface area of the lithium coating, which is measured by gas adsorption using the BET (Brunauer, Emmett, Teller) method. These measurements were carried out using an ASAP 2020 instrument from Micromeritics. Due to the high reactivity of metallic lithium, rare gases such as argon / liquid argon are used as measuring gases. The measurements are carried out in accordance with ISO 9277 ("Determination of the specific surface area of solids by gas adsorption-BET"). The lithium layer produced by the method according to the invention has a surface area of 500 to 20,000 cm 2 / g Li, preferably 1,000 to 10,000 cm 2 / g range of specific surface area.
[0025] Commercially available industrial lithium metal or preferably purer battery or alloy grade lithium is used as the lithium source. Such metal grades are available, for example, from Sigma-Aldrich-Fluka (SAF). For example, there is a 99% "high sodium" technical grade whose metal impurities do not exceed 15,000 ppm, of which the proportion of sodium is by far the highest. On the other hand, transition metals (especially Fe, Ag, Cu, Zn) are only present in the low ppm range (1-20 ppm). The total amount of transition metal impurities is mostly in the range of 100 ppm and below. In addition, battery-quality lithium can be obtained from SAF, i.e., a lithium content (based on metal trace elements) of 99.9%. This particularly pure battery-grade material contains up to 1500 ppm of foreign metal impurities, of which sodium also predominates.
[0026] For the process according to the invention, preference is given to using metallic lithium with a total transition metal impurity content of not more than 200 ppm, particularly preferably not more than 100 ppm and very particularly preferably not more than 50 ppm. On the other hand, impurities of main group metals, in particular alkali metals and alkaline earth metals and metals of the boron group and carbon group (Groups 13 and 14) do not interfere with the process in principle. They can therefore also be present in greater contents, i.e. up to the percentage range.
[0027] The thermal decomposition or dissociation of the lithium-ammonia solutions and compounds used, in particular the defined lithium bronzes, can take place in the presence of additional organic solvents, such as hydrocarbons or ethers or amines, or in the absence of such additives. In particular, saturated aliphatic hydrocarbons such as pentane, hexane, heptane, octane or the common, commercially available mixtures of such compounds (technically "petroleum ether", "white oil", "gasoline") are suitable as organic solvents. Aromatic hydrocarbons can be used to a limited extent. The latter promote undesirable decomposition and the formation of lithium amide. Ether compounds such as diethyl ether, dibutyl ether, methyl tert-butyl ether, tetrahydrofuran, methyltetrahydrofuran, tetrahydropyran, glyme, etc. can also be used, but are not as preferred as the use of hydrocarbons.
[0028] Due to the high reactivity of metallic lithium and Li / (NH 3 ) mixtures, all process steps of the lithium coating operation are carried out in an inert gas atmosphere (preferably argon, helium), a pure ammonia atmosphere or under vacuum conditions.
[0029] Freshly deposited metallic lithium from lithium-NH3 compositions is highly reactive to air and moisture. To ensure safe further processing in technical applications (e.g. in battery construction), passivation of the metal surface (i.e. application of a thin protective layer) is another preferred process step. Such process steps involve contact with gaseous or liquid substances which form stable polymers and / or salts when in contact with lithium. Such process steps are described, for example, in WO2011 / 073324A1.
[0030] In particular, an element or compound selected from the group consisting of inorganic compounds consisting of: N2, CO2, CO, O2, N2O, NO, NO2, HF, F2, PF3, PF5, BF3, POF3, H3PO4, or a liquid organic compound / solvent / solution (coating agent) selected from the group consisting of: carbonates; chelated lithium borate solutions as solutions in organic solvents; organic sulfur compounds; nitrogen-containing organic compounds; organic phosphorus-containing compounds; partially fluorinated hydrocarbons; silicon-containing organic compounds. The organic solvents mentioned are preferably selected from the group consisting of: oxygen-containing heterocycles, carbonates, nitriles, carboxylates or ketones; the organic sulfur compounds are preferably selected from the group consisting of: sulfites, sulfones, sultones. As chelated lithium borate, lithium bis(oxalato)borate (LiBOB) is preferably used.
[0031] Example
[0032] Example 1 : Applying an ultra-thin gold layer on copper foil
[0033] The 8 μm thick copper foil with a diameter of 9 mm produced by Landt Instruments was coated on both sides with ultra-thin (80 nm) gold foil produced by Nanjing Gold Foil Factory, and gently pressed with a soft stamp to bond the metal foils together without bubbles.
[0034] Example 2 : Deposition of lithium metal thin film on copper sheet
[0035] A 12 μm thick copper sheet (10×10 mm) coated on both sides with a 80 nm thick gold layer was placed in an Ar-filled glove box. There, it was contacted (immersed) with lithium bronze for about 20 seconds at ambient temperature (25° C.). Thereafter, the sheet was transferred to a desiccator filled with Ar and the ammonia was completely removed at first 500 mbar and then full oil pump vacuum (0.01 mbar). After this treatment, the sheet exhibited a uniform silver color. By SEM examination of a cross section of the sheet, the thickness of the lithium layer was determined to be about 5 μm.
[0036] The specific surface area of the lithium layer on the top surface was determined by BET to be 1,800 cm 2 / g.
[0037] Example 3 : Gold layer applied using a sputtering process
[0038] A copper sheet with a thickness of 20 μm and a width of 15 mm was gold sputtered in a Leica high vacuum sputter coater (model EMACE 600). Argon was used as the sputtering gas and the sputtering time was 15 minutes.
[0039] The thickness of the gold layer was determined to be 60 nm by high-resolution SEM examination of a cross section of the foil.
[0040] Example 4 : Deposition of lithium metal thin films on Au sputtered copper sheets
[0041] A 20 μm thick copper sheet (15×10 mm) prepared according to Example 3 and coated on one side with a 60 nm thick gold layer was placed in an Ar-filled glove box at ambient temperature (25° C.) and contacted (immersed) with lithium bronze for about 100 seconds. Thereafter, the sheet was transferred to a desiccator filled with Ar and the ammonia was completely removed at first 500 mbar and then full oil pump vacuum (0.01 mbar). After this treatment, the sheet exhibited a uniform silver color. By SEM examination, it was determined that the thickness of the lithium layer was about 8 μm.
[0042] The specific surface area of the lithium layer on the top surface was determined by BET to be 2,100 cm 2 / g.
Claims
1. A method for forming a catalyst having a composition of Li(NH3) on a conductive substrate consisting of a flaky metal or a flaky carbon-based material. 4+x A method for depositing dense lithium from a liquid lithium-ammonia composition, wherein x=0-10, characterized in that The conductive substrate is coated on at least one side by applying an intermediate layer 1-5000 nm thick, the intermediate layer containing at least one metal or metalloid element selected from the group consisting of Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ge, Ga, In, Mg, Cr, V, Mo, W, Zr, Mn, or consisting of at least one such element, and the construction is made with a Li(NH3) 4+x contacting a lithium / ammonia composition wherein x=0-10, and subsequently completely removing the ammonia.
2. The method according to claim 1, characterized in that The lithiophilic conductive substrate is reacted with a Li(NH3)-containing conductive substrate at an ambient temperature in the range of -40 to +40°C, preferably in the range of -10 to +30°C, more preferably in the range of +15 to +30°C, and particularly preferably in the range of +20 to +30°C. 4+x The lithium / ammonia composition of (x=0-10) is contacted for a period of 0.1 to 10,000 seconds, preferably 1 to 2,000 seconds.
3. The method according to any one of claims 1 or 2, characterized in that The ammonia is removed by flooding with an inert gas at a temperature of −40 to +100° C. or under reduced pressure in the range of 0.001 to 700 mbar in the same temperature range, so that the remaining lithium is deposited uniformly, areally and densely on the deposition substrate.
4. The method according to any one of claims 1 to 3, characterized in that The ammonia is removed at a temperature of -20 to +80°C.
5. The method according to any one of claims 1 to 4, characterized in that Lithium bronze having the composition Li(NH 3 ) 4 is preferably used as the lithium / ammonia composition.
6. The method according to any one of claims 1 to 5, characterized in that The lithium-philic interlayer is deposited on the substrate by a method selected from the following: (a) PVD deposition, b) electrochemical thin film deposition, or c) Mechanical deposition The intermediate layer comprises or consists of at least one metal or metalloid element selected from the group consisting of: Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ge, Ga, In, Mg, Cr, V, Mo, W, Zr, Mn, preferably Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ga, In and Mg, more preferably Zn, Al, Au, Si, Sn, Ga and In.
7. The method according to any one of claims 1 to 6, characterized in that The lithium coating layer composed of the dense metallic lithium has a carbonyl content of 500 to 20,000 cm-1 as measured by a BET method using a rare gas. 2 / g Li, preferably 1,000 to 10,000 cm 2 / g Li specific surface area.
8. The method according to claims 1 to 7, characterized in that The metallic lithium deposited on the lithiophilic intermediate layer has a layer thickness determined by SEM of 0.01 to 50 μm, preferably 0.1 to 30 μm, particularly preferably 0.5 to 25 μm.
9. The method according to claims 1 to 7, characterized in that As the electrically conductive substrate, a planar structure consisting of copper, nickel, iron or a foil consisting of or containing carbon nanotubes (CNT) or graphene is used.
10. The method according to claims 1 to 9, characterized in that The surface passivation of the lithium-coated or lithium alloy conductive substrate is carried out by contact with a gaseous or liquid coating agent or a liquid organic coating agent, wherein the gaseous or liquid coating agent is selected from the group consisting of inorganic compounds selected from the following: N2, CO2, CO, O2, N2O, NO, NO2, HF, F2, PF3, PF5, BF3, POF3, H3PO4; the liquid organic coating agent is selected from the group consisting of: carbonates; chelated lithium borate solutions as solutions in organic solvents; organic sulfur compounds; nitrogen-containing organic compounds; organic phosphorus-containing compounds; partially fluorinated hydrocarbons; silicon-containing organic compounds.
11. The method according to claim 10, characterized in that The organic solvent is selected from the group consisting of oxo acid esters, nitriles, carboxylic acid heterocycles, carbonates or ketones, and the organic sulfur compound is selected from the group consisting of sulfites, sulfones, sultones.
12. A conductive substrate coated with dense lithium, wherein the substrate is composed of a sheet metal or a sheet carbon-based material, characterized in that: A lithium-philic interlayer with a thickness of 1 to 5000 nm is provided on at least one side of the substrate, wherein the lithium-philic interlayer contains at least one metal or metalloid element selected from the group consisting of Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ge, Ga, In, Mg, Cr, V, Mo, W, Zr, and Mn or is composed of the at least one metal or metalloid element.
13. The substrate according to claim 12, characterized in that The metal or metalloid element is selected from Zn, Al, B, Cd, Au, Ag, Si, Pb, Sn, Ga, In and Mg, more preferably Zn, Al, Au, Si, Sn, Ga and In.
14. The substrate according to claim 12 or 13, characterized in that The lithium coating layer of the dense metallic lithium has a specific surface area of 500 to 20,000 cm-1 as measured by a BET method using a rare gas. 2 / g Li, preferably 1,000 to 10,000 cm 2 / gLi.
15. The substrate according to any one of claims 12 to 14, characterized in that The metallic lithium deposited on the lithiophilic intermediate layer has a layer thickness determined by SEM of 0.01 to 50 μm, preferably 0.1 to 30 μm, particularly preferably 0.5 to 25 μm.
Citation Information
Patent Citations
Surface-passivated lithium metal and method for the production thereof
WO2011073324A1
Process for the preparation of lithium metal and lithium alloy mouldings
WO2021245196A1